2004
DOI: 10.1021/jp048838m
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Calcium Ion in Polar Solvents:  An X-ray Diffraction and ab Initio Study

Abstract: Ab initio calculations and X-ray diffraction experiments were carried out to study the structure of solutions of calcium chloride in water and methanol. Ab initio calculations were performed at MP2 level and density functional calculations at B3LYP level on calcium-water and calcium-methanol clusters yielding the formation of stable calcium-water clusters with up to eight water molecules and calcium-methanol clusters with up to seven methanol molecules. The experiments were performed in a wide concentration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
177
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(229 citation statements)
references
References 49 publications
50
177
2
Order By: Relevance
“…A comparison of the radial distribution functions for the cations in aqueous and methanolic solutions shows that the average distance to the methanol's oxygen is almost the same as to the water's oxygen. Such feature is in good agreement with the experimental results (Megyes et al, 2004;Neilsen & Enderby, 1979). The first peaks of all ion-oxygen functions in methanolic solutions are higher that those in aqueous solutions.…”
Section: Radial Distribution Functions For the Ionssupporting
confidence: 91%
See 2 more Smart Citations
“…A comparison of the radial distribution functions for the cations in aqueous and methanolic solutions shows that the average distance to the methanol's oxygen is almost the same as to the water's oxygen. Such feature is in good agreement with the experimental results (Megyes et al, 2004;Neilsen & Enderby, 1979). The first peaks of all ion-oxygen functions in methanolic solutions are higher that those in aqueous solutions.…”
Section: Radial Distribution Functions For the Ionssupporting
confidence: 91%
“…The first shell of Ca 2+ is larger; it contains eight or more water molecules and does not show any regularity (Owczarek et al, 2007). X-ray diffraction studies (Tamura et al, 1992, Megyes et al, 2004 have suggested that all these cations are sixcoordinated in methanolic solutions thus their shells are octahedral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CN values and distances from calcium ion to water oxygen atom are in agreement with the experimental data that show a high CN (6 -10) with reported distances of 2.39 -2.46 Å. 56 In addition to examining the coordination of copper ions in the central QM1 active zone we have further investigated the reduced electron density gradient (Fig. 8) using the NCIPlot program.…”
Section: Hybrid Qm/mm MD Energy Conservationsupporting
confidence: 83%
“…Its position coincides with the distance 0.41 nm extracted from X-ray scattering [26]. The first and second maxima of g MgO are well separated, thus the number of water molecules in the second shell can be determined unambiguously.…”
Section: Structure Of the Hydration Shells Of The Metal Ionssupporting
confidence: 73%